"Oh Mohammed, Are You Still Awake?": Admiel Kosman, Martin Buber, and the Poetics of Engagement. Issue 1 (24th April 2019) - Shreiber, Maeera Y.
Abstract : An award-winning poet, an accomplished Talmudist, and a frequent contributor to the pages of Haaretz, Admiel Kosman is hardly new to the scene of contemporary Hebrew letters. However, his work only recently became accessible to English readers when the first translated volume of his poetry appeared in 2011. Reading his work within the context of Martin Buber, whom Kosman regards as his "rebbe, " one discovers a profound challenge to principles of relation—political as well as personal—that are grounded in fixed categories of identity and belonging. Drawing upon the Song of Songs, which whispers throughout his work, Kosman offers us a strong counterresponse to the dominant model of the lyric monologue, with a poetics that aspires towards the dialogic.